General Practice Reformative Agenda, 2024 - Shrestha, Ashis; Ghimire, Rajan; Bajracharya, Sumana; Bom, Rabin; Samal, Anup; Dangal, Binod; Maharjan, Kripa; Maharjan, Rony; Raj Bhandari, Bibek; Joshi, Arabind; Kharal, Puspa Mani; Dawadi, Bishwa Raj; et al. (Journal of General Practice and Emergency Medicine of Nepal, 2024)
Introduction: General Practice, a longstanding specialty in Nepal, requires reformation due to changing professional context and growing health needs of the country. This study aims to identify key areas supported by evidence for the reformation of GP in the country.Method: A qualitative study based on grounded theory was designed to explore the area of general practice and emergency medicine physician’s working in Nepal. Focused group discussions, key-person interviews, polls, and debates were conducted. In the first round, key issues were identified, and in the second round, potential solutions were explored. Data was collected from 15 January to 23 March 2024. There was a panel discussion during the conference of General Practice and Emergency Medicine Association of Nepal in March 2024.Result: Ten important themes that are important to reform the General Practice and Emergency Medicine physcian’s situation in Nepal were identified. Important themes include: leading primary health care service considering a one-door policy, defined roles in all three tiers of health care system, adequate job posts, career ladder in sub-specialty, incorporating primary and emergency healthcare in academic curriculum, developing consistent competency based academic curriculum, advocacy for research wing in the association, ensuring primary teacher position during post graduate trainings, inclusion of general practice and emergency medicine subject in undergraduate curriculum, continuous knowledge and skill enhancement, and standardize specialty name.Conclusion: This study has identified key areas to reformation which included diverse range of academics, curriculum, professional roles, job security, and research.